Theoretical models for chronotherapy: Periodic perturbations in hyperchaos - Juvencio Alberto Betancourt-Mar; Víctor Alfonso Méndez-Guerrero; Carlos Hernández-Rodríguez; José Manuel Nieto-Villar (Mathematical Biosciences and Engineering)
In this work, a hyperchaotic system was used as a model for chronotherapy. We applied a periodic perturbation to a variable, varying the period and amplitude of forcing. The system, five-dimensional, has until three positive Lyapunov exponents. As a result, we get small periodical windows, but it was possible to get large areas of hyperchaos of two positive Lyapunov exponents from a chaotic behavior. In this chronotherapy model, chaos could be considered as a dynamical disease, and therapy goal must be to restore the hyperchaotic state.